The Effects of Immigration Enforcement on Student Outcomes in a New Era of Immigration Policy in the United States - David Figlio; Umut Ozek (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This study presents the first evidence, to our knowledge, of the effects of the surge in interior immigration apprehensions in 2025 in the United States on student academic performance using detailed student-level administrative records from Florida. We find evidence that immigration enforcement reduced test scores for both U.S.-born and foreign-born Spanish-speaking students while also reducing the likelihood that these students are involved in disciplinary incidents in schools. Both of these effects are more pronounced for students in middle and high schools.
Keywords: I20; 330; immigration enforcement; recent immigrants; immigrant students; human capital